2010
DOI: 10.1158/0008-5472.can-10-1358
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of Biomarkers to Predict Systemic Progression in Men with High-Risk Prostate Cancer Treated Surgically Is Dependent on ERG Status

Abstract: The objective of this study was to assess the relationship of the tumor protein levels of TOP2A and MIB-1 and ERG status with cancer-specific outcomes in men with high-risk prostate cancer treated by radical prostatectomy (RP). A 150-pair case-control study was designed from RP patients who developed systemic progression (SP) within 6 years of RP (cases) and men who were free of disease at least 8 years after RP (controls). The cases and controls were matched on conventional prognostic clinical parameters. TOP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 31 publications
5
47
2
1
Order By: Relevance
“…Attard and colleagues (49) showed that men with androgen-resistant cancers had a higher maximal prostatespecific response when treated with the antiandrogen abiraterone acetate if the tumors were ERG-positive compared with ERG-negative tumors. This is also in the line with a recent study by Karnes and colleagues (50), which showed that patients with ERG-positive tumors showed a more significant treatment effect in response to adjuvant androgen deprivation than patients with ERG-negative tumors. This could be due to the fact that ERG-positive tumors are particularly dependent on a functional AR because ERG can only be overexpressed in the presence of AR.…”
Section: Discussionsupporting
confidence: 92%
“…Attard and colleagues (49) showed that men with androgen-resistant cancers had a higher maximal prostatespecific response when treated with the antiandrogen abiraterone acetate if the tumors were ERG-positive compared with ERG-negative tumors. This is also in the line with a recent study by Karnes and colleagues (50), which showed that patients with ERG-positive tumors showed a more significant treatment effect in response to adjuvant androgen deprivation than patients with ERG-negative tumors. This could be due to the fact that ERG-positive tumors are particularly dependent on a functional AR because ERG can only be overexpressed in the presence of AR.…”
Section: Discussionsupporting
confidence: 92%
“…In concert with other publications showing the potential predictive value of TMPRSS2-ERG status on ADT response (18,35,36), ERG overexpression was reported to be a factor in the relative response to salvage ADT following surgery (19). However, in our subgroup of patients treated with ADT, neither TMPRSS2-ERG fusion nor ERG overexpression predicted outcome.…”
Section: Resultssupporting
confidence: 80%
“…Karnes and colleagues have proposed that ERGpositive patients present a better response to androgen deprivation (36) and, recently, TMPRSS2-ERG status has been shown to be a predictive biomarker for androgen therapy in the form of abiraterone (46). As such, our results could differ in patients receiving combined modality therapy as the primary treatment (e.g., high-risk or locally advanced prostate cancer) in which fusion status could be studied in the context of the need for salvage ADT (including enzalutamide or abiraterone) or systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…While TOP2A has been extensively studied in tumor samples, such as breast cancer, prostate cancer, gastric cancer, and ovarian cancer, [25][26][27][28] its role in carcinogenesis …”
Section: Discussionmentioning
confidence: 99%